Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Surfactant tunable hierarchical nanostructures of CdIn2S4 and their photohydrogen production under solar light - Bhirud, Ashwini P.; Chaudhari, Nilima; Nikam, Latesh; Sonawane, Ravindra; Patil, Kashinath; Baeg, Jin-Ook; Kale, Bharat (International Journal of Hydrogen Energy, 2011)
The hierarchical nanostructures of CdIn2S4 were selectively prepared through hydrothermal process in the presence of different surfactants. Structural study demonstrated existence of cubic spinel structure and micro structural study shown a pretty marigold flower like morphology without any surfactant. The effect of surfactants on the morphology and microstructure of CdIn2S4 has been studied by using Polyvinyl pyrrolidone (PVP) and Cetyltrimethyl ammonium bromide (CTAB) as a surfactants. The CdIn2S4 bipyramids with length of 0.7-1 mu m have been obtained using PVP. Interestingly, the nanopetals (thin and transparent) of CdIn2S4 are self assembled into hollow spheres in the presence of CTAB. Considering the importance of these unique nanostructures, the growth mechanism has also been proposed. The optical properties demonstrated the band gap in the range of 2.12-2.29 eV which is well within the visible region. In this contest, photocatalytic activity for hydrogen production using the above nanostructures under visible light was also demonstrated. The prima-fascia observations shows that the bipyramidal CdIn2S4 exhibit excellent photocatalytic activity for hydrogen production (3238 mu molh(-1)) than other nanostructures. Being a nanostructured semiconductor chalcogenide with a good stability will also have potential applications in solar cells and LED. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bipyramids; CdIn2S4; Hydrogen generation; hydrothermal; Self-assembled

Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.

Situ preparation of N-TiO2/graphene nanocomposite and its enhanced photocatalytic hydrogen production by H2S splitting under solar light - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Ambekar, Jalindar D.; Park, Chan-J.; Kale, Bharat B. (Nanoscale, 2015)
Highly monodispersed nitrogen doped TiO2 nanoparticles were successfully deposited on graphene (N-TiO2/Gr) by a facile in-situ wet chemical method for the first time. N-TiO2/Gr has been further used for photocatalytic hydrogen production using a naturally occurring abundant source of energy i.e. solar light. The N-TiO2/Gr nanocomposite composition was optimized by varying the concentrations of dopant nitrogen and graphene (using various concentrations of graphene) for utmost hydrogen production. The structural, optical and morphological aspects of nanocomposites were studied using XRD, UV-DRS, Raman, XPS, FESEM, and TEM. The structural study of the nanocomposite shows existence of anatase N-TiO2. Further, the details of the components present in the composition were confirmed with Raman and XPS. The morphological study shows that very tiny, 7-10 nm sized, N-TiO2 nanoparticles are deposited on the graphene sheet. The optical study reveals a drastic change in absorption edge and consequent total absorption due to nitrogen doping and presence of graphene. Considering the extended absorption edge to the visible region, these nanocomposites were further used as a photocatalyst to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-TiO2/Gr nanocomposite with 2% graphene exhibits enhanced photocatalytic stable hydrogen production i.e. similar to 5941 mu mol h(-1) under solar light irradiation using just 0.2 gm nanocomposite, which is much higher as compared to P25, undoped TiO2 and TiO2/Gr nanocomposite. The enhancement in the photocatalytic activity is attributed to `N' doping as well as high specific surface area and charge carrier ability of graphene. The recycling of the photocatalyst shows a good stability of the nanocomposites. This work may provide new insights to design other semiconductor deposited graphene novel nanocomposites as a visible light active photocatalyst.

Situ preparation of N-ZnO/graphene nanocomposites: excellent candidate as a photocatalyst for enhanced solar hydrogen generation and high performance supercapacitor electrode - Bhirud, Ashwini P.; Sathaye, Shivaram; Waichal, Rupali; Park, Chan-Jin; Kale, Bharat (Journal of Materials Chemistry A, 2015)
We have demonstrated a facile in situ wet chemical method to synthesize nanostructured nitrogen doped ZnO/Graphene (N-ZnO/GR) nanocomposites for the first time. Nitrogen doped ZnO over graphene (N-ZnO/GR) was studied using various concentrations of graphene. During the synthesis of N-ZnO/GR nanocomposites, in situ formation of graphene via GO reduction and formation of 4-9 nm N-ZnO have been demonstrated. The composite N-ZnO/GR absorbs in the visible region and this property is used for the photocatalytic reaction to transform hazardous H2S waste into eco-friendly hydrogen using solar light. The N-ZnO/GR nanocomposite with 0.3% graphene exhibits an enhanced photocatalytic stable hydrogen production rate i.e. similar to 5072 mu mol h(-1) under visible light irradiation. It is noteworthy that the N-ZnO/GR electrode exhibits a high specific capacitance of 555 F g(-1) and excellent cyclic performance with nearly 96.20% capacity retention after 2000 cycles at a current density of 10 A g(-1). These results indicate great potential applications of N-ZnO/GR in developing high hydrogen production and supercapacitors with high energy and power densities.